Cervicothoracic Intradural Arachnoid Cyst Misdiagnosed as Motor Neuron Disease - P. G. Sämann; H. Himmerich; T. Merl; C. Erös; M. B. Müller; J. C. Tonn; B. Buchwald (Case Reports in Medicine)
Recognizing syndromes which mimic ALS is crucial both to avoid giving this diagnosis erroneously and since there may be appropriate treatments. We report a 63-year-old woman diagnosed with possible ALS five years ago based on upper and lower motor neuron signs with typical electrophysiology and normal cranial MRI. At reassessment, spinal MRI revealed a cervicothoracic cyst with cord compression that was successfully treated neurosurgically. Histopathology confirmed an arachnoid origin as suspected from MRI. Spinal cysts may mimic ALS and need to be thoroughly excluded by appropriate imaging.